Comparison of bio-chars formation derived from fast and slow pyrolysis of walnut shell. (1st February 2020) - Yuan, Tong; He, Wenjing; Yin, Guojun; Xu, Shiai
Graphical abstract: Highlights: The fast and slow pyrolysis of walnut shell at 400–800 °C was studied. The formation mechanism of bio-char in fast pyrolysis is almost the same as that in slow pyrolysis. The quinone group content could be used as a signal to exhibit the stabilization of oxygen in bio-char. The bio-char in the fast pyrolysis is easier for microcrystalline. Abstract: Fast and slow pyrolysis are good means of biomass transformation. Studying the formation of bio-char is not only helpful to intensify the transformation of biomass, but also to improve its performance. However, little work has been reported on the similarities and differences of bio-chars in fast and slow pyrolysis. We investigated the fast and slow pyrolysis of walnut shell at 400–800 °C to find the evolvement law of bio-char. It was found that the formation mechanism of bio-char in fast pyrolysis is almost the same as that in slow pyrolysis. There are two stages in the formation of bio-char: the generation of free radicals caused by the covalent bond breaking at temperature less than 600 °C; the reduce of free radicals through the condensation reactions from 600 to 800 °C. The contents of various oxygen-containing functional groups presented regularity with the increase of pyrolysis temperature, in which the quinone group increases with the pyrolysis temperature increasing, which phenomenon could be used as a signal to exhibit the stabilization of oxygen in bio-char. The bio-char yields, free radicals and quinone contents are slightly higher in slow pyrolysis. The graphite crystals in bio-char have the tendency of microcrystallization with the increase of temperature, in which progress the fast pyrolysis has superiority at the low temperature.